In the footsteps of Inkarri - Huamán López, Carlos (2020)
The Inkarri myth represents the vindicating spirit of the subjugated and humiliated Quechua sociocultural universe. However, its scope is not limited to the world represented, but also to others who have suffered political, social and cultural subjection. It is a current myth with roots in the colonial past. It underlies the memory and the collective imagination, and is manifested through oral stories, poems and songs, with variations that maintain the central axis of the argument.